Addressing aspect interactions in an industrial setting: experiences, problems and solutions - Zambrano Polo y La Borda, Arturo Federico (2013)
Aspect oriented programming (AOP) introduces new and powerful modularization constructs. The aspect module is used to encapsulate crosscutting concerns, which otherwise would remain tangled and scattered. The idea of encapsulating crosscutting concerns rapidly expanded to earlier phases in the development cycle, including requirement analysis (aspect oriented requirement engineering, AORE) and design (aspect oriented modeling, AOM). The overall application of aspect orientation concepts is known as aspect oriented software development (AOSD). AOP is not yet a mainstream practice. Particularly AOSD is still in its early stages. This is reflected in the lack of reports of full development cycles using aspect oriented approaches, especially using industrial case studies. Furthermore, the power of aspects comes at the price of new challenges, one of them is that systems built using aspects are more difficult to understand. The crosscutting nature of aspects allows them to alter the behavior of many other modules. As a result, aspects may interact in unintended and unanticipated ways. This problem is known as aspect interactions. In this work we deal with the aspect interaction problem in the context of an industrial domain: slots machines. We perform a complete development cycle of the slot machine software. This is, to the best of our knowledge, the first complete industrial case of study of aspect orientation. Through this experience we discovered the limitations with regard to aspect interactions, of some emblematic aspect oriented approaches for requirement engineering, design and implementation. The contribution of this work is threefold. Firstly, we contribute with the evaluation and extensions to some of AORE and AOM approaches, in order to provide explicit support for aspect interactions in requirement analysis and design phases. We also evaluate the implementation of interactions using a static and a dynamic AOP language, and propose an AspectJ extension that copes with aspect interactions. Secondly, this work is the first report of a complete aspect oriented development cycle of an industrial case study. Thirdly, this work provides a complex case study that presents several business logic crosscutting concerns, which in turn exhibit numerous aspect interactions, that serves as a challenging test bed for upcoming AOSD approaches.